Anger Status and its Dimensions among High School Female Students: A Cross-Sectional Study - Amin Mirzaei; Zeinab Soleimapour; Mohsen Jalilian; Mohammad Sadegh Abedzadeh Zavareh (Journal of Education and Community Health)
Aims: Anger is one of the excitements of human, which, if left out of a balanced level and transformed into aggressive behavior, has many negative effects on all aspects of the health of individuals. Awareness of anger status in adolescent students and its effective factors can be the first step in planning and implementing psychological interventions to control and management of students’ anger. The aim of the present study was to determine the status of anger in high school girl students in Ilam. Instrument & Methods: This cross-sectional descriptive study was conducted on 313 high school girl students in Ilam in 2017 who were selected by multi stage random sampling method. Data were collected using Spielberger's Anger Scale (STAXI-2) in the form of self-reported, and were analyzed by SPSS 19 software using Pearson correlation and Kendall correlation tests, independent t-test and one-way ANOVA. Findings: The mean scores of anger state and anger trait in first-grade students was significantly lower than the other two grades (p=0.001). Also, the general anger expression in students with laborer or unemployed parents was significantly higher than other students (p=0.032). There was a positive significant correlation between general anger expression index with anger state and anger trait indexes (p<0.01). Conclusion: The general anger expression and anger trait in the studied students is moderate and their grade of students’ education and their parents' occupation are effective factors on the anger of these students.